Bibliometric Mapping of Financial Management Research: Trends, Themes, and Future Directions - Fadhilah, Resky Nur (LPPPIPublishing, 2025)
This study aims to map the development of financial management research through a bibliometric analysis using data obtained from Crossref and Google Scholar. The analysis covers the period from 2010 to 2024 and focuses on relevant publications in the field of financial management. The methodology includes the examination of publication trends, citation patterns, co-authorship networks, and keyword co-occurrence mapping using VOSviewer software. The findings reveal a significant increase in the volume of publications on financial management, with a thematic shift from traditional topics such as capital structure, dividend policy, and risk management toward more contemporary issues including financial technology (FinTech), sustainable finance (ESG), and financial digitalization. Furthermore, the results indicate a growing level of international and institutional collaboration, particularly across Asia and Europe. This study provides valuable insights into the intellectual landscape and future directions of financial management research, serving as a useful reference for scholars, academics, and practitioners.